Ab Initio Determination of Atomic Structure and Stark Broadening Parameters: Pb IV and Recent Results - Hamdi R.; Nessib N. Ben; Dimitrijević M. S.; Sahal-Bréchot S. (Open Astronomy, 2011)
We present a review of our previous ab initio calculations of Stark broadening parameters using semi-classical perturbation method for the calculation of Stark widths and shifts, and the SUPERSTRUCURE (SST) code for the determination of atomic structure. SST code takes into account the configuration interactions and relativistic effects. New results are also presented for some spectral lines of Pb IV. Energy levels and oscillator strengths are calculated using Hartree-Fock relativistic approach, and the Stark broadening parameters are determined using a semiclassical perturbation approach.